2018
DOI: 10.1021/jacs.8b03626
|View full text |Cite
|
Sign up to set email alerts
|

Main-Group-Catalyzed Reductive Alkylation of Multiply Substituted Amines with Aldehydes Using H2

Abstract: Given the growing demand for green and sustainable chemical processes, the catalytic reductive alkylation of amines with main-group catalysts of low toxicity and molecular hydrogen as the reductant would be an ideal method to functionalize amines. However, such a process remains challenging. Herein, a novel reductive alkylation system using H is presented, which proceeds via a tandem reaction that involves the B(2,6-ClCH)( p-HCF)-catalyzed formation of an imine and the subsequent hydrogenation of this imine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 58 publications
2
59
0
Order By: Relevance
“…Several protocols are adopted to install alkyl groups on the amine nitrogen, including reductive alkylation using carbon dioxide and carboxylic/carbonic acid derivatives, transition metal catalysed N‐nucleophilic substitution to alcohols, hydrogen borrowing methodology by heterogeneous catalysis, late‐transition and non‐precious metal catalysed hydroamination and hydroamidation processes etc [11] . However, the recent focus on green, sustainable and low‐toxic catalytic processes have highlighted novel alkylation of amines employing H 2 as a reducing agent and readily available Lewis acidic triarylboranes as catalyst [12] . In fact, tris(pentafluorophenyl)borane have lately been employed as an effective Lewis acid catalyst for a variety of synthetic conversions [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several protocols are adopted to install alkyl groups on the amine nitrogen, including reductive alkylation using carbon dioxide and carboxylic/carbonic acid derivatives, transition metal catalysed N‐nucleophilic substitution to alcohols, hydrogen borrowing methodology by heterogeneous catalysis, late‐transition and non‐precious metal catalysed hydroamination and hydroamidation processes etc [11] . However, the recent focus on green, sustainable and low‐toxic catalytic processes have highlighted novel alkylation of amines employing H 2 as a reducing agent and readily available Lewis acidic triarylboranes as catalyst [12] . In fact, tris(pentafluorophenyl)borane have lately been employed as an effective Lewis acid catalyst for a variety of synthetic conversions [13] .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent experimental effort, Ogoshi and others have shown that triarylborane, B(2,6‐Cl 2 C 6 H 3 )( p ‐HC 6 F 4 ) 2 ( BAr 3 ), catalyses the condensation of aniline ( An ) and benzaldehyde ( Bz ) in presence of molecular H 2 to synthesize the desired N ‐phenylbenzylamine ( Am ) with the intermediacy of N ‐benzylideneaniline ( Im ) (Scheme 1) in THF solvent [12] . Interestingly, this strategy has widespread applications and broader substrate scope, like in the alkylation of amino acids and their derivatives [12] . Furthermore, utilization of H 2 as the reductant offers generation of H 2 O as the sole by‐product, in congruence to the “greenness” of this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Tris(pentauorophenyl)borane has recently emerged as a powerful Lewis acid catalyst. [1][2][3] The strong Lewis acidity 2,3 at the boron center allows us to establish a wide range of organic transformations via C-B, [4][5][6] C-C, [7][8][9][10] C-N, 11,12 C-O 13,14 and C-Si [15][16][17][18] bond formations. Pioneered by Stephan and Erker, B(C 6 F 5 ) 3 has gained popularity in frustrated Lewis pair (FLP) chemistry which encompasses widespread applications in organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Additionally, only seven reports described reactions involving their secondary counterparts (R 2 NBR 2 ). [2][3][4][5][6] Herein we report that primary aminoboranes are powerful tools for the mild and chemoselective preparation of aldimines, [7][8][9] especially those hard to access with previous methods. [10] We hypothesized that primary aminoboranes should be sufficiently Lewis acidic to react with aldehydes to afford unstable hemi-aminals B;t he latter would eliminate boronic acid giving access to aldimines C (Scheme 1).…”
mentioning
confidence: 99%
“…Using our optimized conditions [1:1 ratio of aminoborane to aldehyde in C 6 D 6 (1.1m)a t2 5 8 8C],w ee xamined the substrate scope (Scheme 2). With respect to the substituents on nitrogen this methodology is readily applicable to avariety of amines featuring different steric and electronic properties (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), and even to hydrazines (14). Although aminoboranes derived from very electron poor anilines (7,8)e xhibit lower conversions this is circumvented by using 2equivalents of the corresponding aminoborane.W ith respect to aldehydes,t he reaction is widely applicable to both alkyl-and aryl-aldehydes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%